The biomechanics of cranial forces during figure skating spinning elements - Wang, D. H.; Kostyun, R. (The Professional Skater PS Magazine, 2015)
Several facets of figure skating, such as the forces associated with jumping and landing, have been qualitatively evaluated, but a comprehensive biomechanica! understanding of the forces related with spinning has yet to be explored. Figure skaters are a unique group of athletes who generate substantial rotational forces during many of their skating elements. These rotational forces may lead to significant issues including vascular injuries and vestibular dysfunctions. We have begun to investigate these rotational forces using an accelerometer to determine the forces generated in these individuals. We present the results of an observational, biomechanical analysis on thirty healthy figure skaters evaluating four basic spinning elements.